2019
DOI: 10.3390/jcm8050756
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormones and Spermatozoa: In Vitro Effects on Sperm Mitochondria, Viability and DNA Integrity

Abstract: The aim of this study wasto assess the in vitro effects of levothyroxine (LT4) on conventional and bio-functional sperm parameters and its implications on fertility. Patients with male idiopathic infertility were enrolled and subjected to examination of the seminal fluid and capacitation according to the WHO 2010 criteria and flow cytometric sperm analysis for the evaluation of bio-functional sperm parameters. LT4 significantly increased the percentage of spermatozoa with high mitochondrial membrane potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Therapeutic issues are also addressed in this Special Issue. These include the effectiveness of L-acetyl-carnitine for the treatment of asthenozoospermia in patients with type I diabetes mellitus [8] and the in vitro effects of thyroid hormones in sperm mitochondrial function, viability, and DNA integrity [9].…”
mentioning
confidence: 99%
“…Therapeutic issues are also addressed in this Special Issue. These include the effectiveness of L-acetyl-carnitine for the treatment of asthenozoospermia in patients with type I diabetes mellitus [8] and the in vitro effects of thyroid hormones in sperm mitochondrial function, viability, and DNA integrity [9].…”
mentioning
confidence: 99%
“…Many aspects of the possible role of thyroid hormones are yet to be clarified in the dog, by taking also into account their involvement on the reproductive performance. To date, all in vitro researches were performed on animal models, and recently in vitro effects of thyroid hormones on sperm mitochondria, viability and DNA integrity were studied in humans (Condorelli et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, fT 4 seems to have a potential protective effect, being inversely correlated with sperm DNA damage in men (Meeker et al 2008). In human, the in vitro effects of levothyroxine on conventional and bio-functional sperm parameters on male fertility were recently assessed, clarifying the involvement of thyroid function on fertility (Condorelli et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the rat have shown that hypothyroidism causes arrest of spermatogenesis. [ 12 ] In humans, similar studies done till now are heterogeneous, with regards to the number of patients included, the way semen analysis was reported, and whether the posttreatment effect was analyzed or not. Studies on the effect of hypothyroidism on semen parameters done till now show a negligible effect of hypothyroidism on semen volume, except one by Corrales et al ., where a statistically significant difference was found in the mean semen volume between patients and controls (2.7 ± 1.4 vs. 3.7 ± 1.2).…”
Section: Discussionmentioning
confidence: 99%